PHÂN TÍCH ĐỊA ĐỘNG LỰC TRONG NGHIÊN CỨU TAI BIẾN ĐỊA CHẤT BỀ MẶT (LŨ, LŨ QUÉT VÙNG BẮC TRUNG BỘ) - Thắng, Ngô Gia; Bách, Lê Duy (Vietnam Journal of Earth Sciences, 2017)
The paper is dealing with the interactions between the endogenic and exogenic dynamic proccesses. which caussed the "surface layer" of the Eath crust. This surface layer is the place of theoccurence of geological surface hazards including floods and flash floods. The authors synthetically analyse and evaluate the contronling and configuraling influences of the geodynamic procceses in the formation and development of the surface layer aswell as in generation of flood hazards in North Central part of Vietnam. In the other hand, the surface layer is also the field for the human activations, so the more complete knowledge andthe understanding on natural laws as hazards, being in progress on the surface, would be important aid to avoid and diminuate the damages